Subsurface exploration and sampling of soils for civil engineering purposes : report on a research project of the Committe on Sampling and Testing, Soil Mechanics and Foundations Division, American Society of Civil Engineers - Hvorslev, M. Juul (New York : American Society of Civil Engineers)
08